A study on factors that determine firm’s capital structure: a case study of Telekom Malaysia Berhad’s capital structure / Nur Atiqah Balkis Mazlan - Mazlan, Nur Atiqah Balkis (2010)
Difficulties in determining factors related to a firm’s capital structure have long been recognized by a number of authors. Modigliani and Miller (1958, 1963) had started the association of debate between firm’s financial structure and various firm specific factors. Other early research were done by Bradley, Jarrell and Kim (1984), Long and Malitz (1985), Titman and Wassels (1983, 1988), Baskin (1989) and others. This paper is continuity from the previous research. But this research will focus on Malaysia telecommunication firm. This research shed some light on the determinants of the capital structure of largest telecommunication company listed on Bursa Malaysia which is TELEKOM MALAYSIA BERHAD. Research will examine the cross-sectional variation in capital structure among these companies for the time period 2000 until 2009 and include variables that are based on different capital structure theories and had been investigated before. This study sought to examine the determinants of debt to equity ratio. It measures the extent to which observe debt to equity ratio could be significantly predicted by various firms’ specific factors. The research approaches that will be used in this research are Multiple Regression Analysis, Coefficient of Determination, Analysis of Variance (Fstatistic) and T-Statistic. After analyzing the data thoroughly, various results have been produced for the company. The result show that equity financing firms leverage and assets composition have significant relation with TELEKOM MALAYSIA BERHAD’s capital structure where the rest is not.